2012
DOI: 10.1007/s00066-012-0078-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of seed brachytherapy or external beam radiotherapy (70 Gy or 74 Gy) in 919 low-risk prostate cancer patients

Abstract: Low-risk prostate cancer patients receiving 74 Gy by EBRT show comparable biochemical control rates to patients receiving seed brachytherapy, whereas patients receiving 70 Gy show significantly worse outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…The rapid adoption of new RT practices as well as patient preference toward more convenient BT treatments are proposed explanations for the lack of comparative RT trials (13). A large number of retrospective studies have attempted to compare the treatment effectiveness of 2 or more RT modalities (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, interpretation of this retrospective evidence can be challenging because very few studies make direct comparisons in homogenous GUROC low-or intermediate-risk patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid adoption of new RT practices as well as patient preference toward more convenient BT treatments are proposed explanations for the lack of comparative RT trials (13). A large number of retrospective studies have attempted to compare the treatment effectiveness of 2 or more RT modalities (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33). However, interpretation of this retrospective evidence can be challenging because very few studies make direct comparisons in homogenous GUROC low-or intermediate-risk patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…We were, however, able to [26]. There is no doubt that large academic centers of excellence in Europe provide substantial clinical data [27]. As Kupelian et al [3] stated bRFS will "remain an important clinical endpoint even in the absence of data validating as it a surrogate for survival because of its use as a trigger for potentially curative salvage therapies or prolonged AD".…”
mentioning
confidence: 99%
“…Several authors have reported that permanent implants for localized prostate cancer show excellent biochemical control and are associated with less severe toxicities [ 2 17 ]. According to a systematic review of randomized controlled studies, external-beam radiation therapy (EBRT), brachytherapy, and radical prostatectomy were found to be effective in the management of localized prostate cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%